Evaluation of Production Efficiency for Some Cultivated Mushroom Strains Agaricus Bisporus which was Renovated Mother Culture In Multiple Methods - M. Alkaisi, Mustafa R.; A. Hasan, Abdulah; Aljuboori, Ayad W.A. (Iraqi Journal of Science, 2023)
In this study tested the efficiency of three methods (Tissue culture, Multispore, Multispore mixture) to renew isolates of mother culture for cultivated mushroom strains (X20, X25, B62) And prevent it from deterioration and keep or increase productivity, It has been found that the strains in response varied according to the type of method used for the renewal of isolation. It was found that 17.78 kg/m2 higher significant increase in total yield have been achieved when use multispore mix between X20 and B62 strain compared to all of those isolates the mother culture strains, Followed by tissue culture method for the renewal of strains, which amounted to the total yield 14.16 kg/m2 when B62 strain. Multispore method was characterized at the X25strain reaching the total yield to 10.25 kg/m2.